Immune Thrombocytopenia: A Rare Haematological Manifestation of Sarcoidosis - Monteiro, Manuel (2022)
Sarcoidosis is a multisystemic granulomatous disorder of unknown aetiology. Although the lungs are the primary site of involvement, the disease can affect virtually any organ, leading to a wide variety of clinical manifestations. Haematological abnormalities are uncommon, and most frequently include lymphopenia and anaemia. Thrombocytopenia, however, is rare, and three distinct pathophysiological mechanisms have been described: immune platelet destruction, splenomegaly with hypersplenism, and bone marrow infiltration. We report a case of sarcoidosis presenting with pulmonary and cutaneous involvement, and severe acute thrombocytopenia. Bone marrow aspirate was consistent with an immune process, assumed as the primary cause for the cytopenia, but bone marrow biopsy also showed multiple noncaseating granulomas, and a CT scan revealed massive splenomegaly. There are no guidelines for the management of thrombocytopenia in sarcoidosis. In our patient, treatment with intravenous immune globulin and corticosteroids restored normal platelet count.